2021
DOI: 10.1186/s12887-021-02547-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of umbilical cord C-peptide levels in early prediction of hypoglycemia in infants of diabetic mothers

Abstract: Background Until now, diabetes during pregnancy has been associated with a high risk of maternal, fetal, and neonatal morbidities and mortalities. The main aim of this study was to evaluate the risk factors of hypoglycemia in infants of diabetic mothers (IDMs) and to study the relationship between umbilical cord (UC) C peptide levels and the risk of developing hypoglycemia. Material and methods UC blood C-peptide and serial serum blood glucose meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(11 reference statements)
2
4
0
Order By: Relevance
“…Regarding the demographic data, three studies examined hypoglycemic versus normoglycemic groups in infants of diabetic mothers. They showed no significant differences in maternal age or weight between these groups, aligning with our findings demonstrated similar results in cases and controls (6)(7)(8). Our findings indicated that the hypoglycemic and normoglycemic groups showed no significant differences in gestational age at birth or 1-minute Apgar scores.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the demographic data, three studies examined hypoglycemic versus normoglycemic groups in infants of diabetic mothers. They showed no significant differences in maternal age or weight between these groups, aligning with our findings demonstrated similar results in cases and controls (6)(7)(8). Our findings indicated that the hypoglycemic and normoglycemic groups showed no significant differences in gestational age at birth or 1-minute Apgar scores.…”
Section: Discussionsupporting
confidence: 91%
“…However, significant differences emerged regarding birth weight and 5minute Apgar scores between the two groups. Similarly, a comparable finding in gestational age and 1-minute Apgar scores between the hypoglycemic and normoglycemic groups but highlighted no significant distinctions in neonatal weight or 5-minute Apgar scores, was noted (6). Additionally, a study (8) reported no significant differences in newborn characteristics between case and control groups, while another (7) found no significant disparities in gestational age and Apgar scores at 1 and 5 minutes between hypoglycemic and normoglycemic groups.…”
Section: Discussionmentioning
confidence: 74%
“…The current analysis reported the significance of cord serum C-peptide levels above P90 (defined as fetal hyperinsulinemia) to increased risks of neurodevelopmental delay. Increasing evidence has indicated that cord blood C-peptide was associated with maternal insulin sensitivity, fetal hyperinsulinemia and/or neonatal hypoglycemia ( 21 , 22 ). There have been few studies to date on the impact of cord serum C-peptide on neurodevelopmental delay.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study, 15 including 83 neonates born to diabetic individuals (35 individuals had GDM, 45 individuals had type 2 diabetes, and 3 had T1D) showed that higher CBCP levels were significantly associated with neonatal hypoglycaemia. The association persisted after adjusting for birthing individual age, diabetes duration, mode of delivery, and birth weight.…”
Section: Discussionmentioning
confidence: 99%